Korelasi kadar bikarbonat dengan QSOFA score pada pasien sepsis di RSUD dr. Doris Sylvanus - Adelia, Sirli; Widayati, Ratna; Surbakti, Ranintha br; Patricia, Tisha; Martani, Natalia Sri (Fakultas Kedokteran Universitas Palangka Raya, 2024)
Sepsis is a life-threatening medical emergency due to organ dysfunction described by the body's systemic immunological response to an infectious reaction. Sepsis patients experience sequential system failure, leading to multiple organ failure Sepsis sufferers experience organ failure will experience metabolic acidosis. An indicator of metabolic acidosis is a decrease in bicarbonate. qSOFA is required to determine the risk of organ failure in sepsis patients. To analyze the correlation of bicarbonate levels with qSOFA score in sepsis patients. The relationship between bicarbonate levels and qSOFA was tested using the Pearson correlation. There was no statistically significant with p value = 0.099 and r value = -0.307. Conclusion: There is no significant relationship between bicarbonate levels and qSOFA scores in sepsis patients at RSUD dr. Doris Sylvanus, there is a low correlation intensity with a negative correlation direction, indicating higher bicarbonate levels, lower qSOFA scores.